Sea urchins in the intertidal zone on Karanrang Island, Pangkep Regency; Density, abundance, community structure, and distribution patterns - Sri Nursyarina Fitri; Hartati Tamti; Mesalina Tri Hidayani; Heriansah Heriansah (Sekolah Tinggi Ilmu Pertanian Wuna, 2023)
Sea urchins were ecologically and economically important biota, but scientific information on sea urchins is still very minimal and there is no ongoing monitoring. The purpose of this study was to determine the density, abundance, community structure, and distribution patterns of sea urchins in the intertidal zone of Karanrang Island, Pangkep Regency. The research in June-July 2022 was carried out at high and low tide using three transects measuring 1 x 1 m consisting of four plots measuring 50 x 50 cm.Â Determination of stations based on information from local residents to get observation stations based on tidal conditions. The results showed that three species of sea urchins from two families were found, namely Diadema setosum, Echinothrix calamaris, and Tripneustes gratilla. The species of D. setosum was found to be very abundant (97.3-97.6%) and tended to be more abundant during high tide than during low tide. The index of diversity and uniformity of porcupine species is low (H' = 0.130-0.142 and E = 0.118-0.129). The species dominance index was in the range of 0.946-0.953 indicating high dominance of D. setosum. Spatially, D. setosum had a uniform distribution pattern, whereas E. calamaris and T. gratilla were distributed in clusters. Further spatial and temporal research is needed to comprehensively determinant the conditions of the sea urchin population on Karanrang Island, Pangkep Regency.